The collected works (gsuṅ-ʼbum) of Yaṅ-dgon-pa Rgyal-mtshan-dpal - Yaṅ-dgon-pa Rgyal-mtshan-dpal, 1213-1258 (Kargyud Sungrab Nyamso Khang, 1973)
Writings on Lamaist meditational and ritual practice by a master of the "Upper" branch of the Drukpa Kargyudpa sect.